Crataegus and Rosa genera in the Solec Basin and southern part of the Pińczów Hummock (Southern Poland) - Sołtys-Lelek, Anna (Biodiversity: Research and Conservation, 2012)
The Crataegus and Rosa genera are critical taxa. Because of difficulties in species identification, nobody has dealt with the distribution of these genera in the Solec Basin (Niecka Solecka) and southern part of the PiOczUw Hummock (Garb PiOczowski) thus far. The aim of this work was prepare a complete list of critical species of these genera in the study area. The floristic studies were carried out in the years 2004-2009. Nineteen species were recorded: 6 hawthorns and 13 roses. Seven species were new for the flora of the studied area (4 roses and 3 hawthorns).